A contribuição de Catharina Crestani Seger na constituição educacional, comercial e política do município de Palma Sola, SC - Lawisch, Marieli (2023)
The present study is located in the Graduate Program in Education - Masters, Campus Francisco Beltrão/PR, of the State University of Western Paraná - Unioeste, area of concentration in Education, Line of Research: Culture, Educational Processes and Training of Teachers. The research theme has as object of study the citizen Catharina Crestani Seger and her contributions to the city of Palma Sola, SC. We verify the performance of the Palmassolense citizen in the area of education, commerce and local politics; in addition to investigating Catharina's performance as a woman in the historical period established between 1951 and 1979, which delimits Catharina's arrival in Palma Sola until the final moment of her life. This research takes the following question as a problem to be investigated: how did Catharina Crestani Seger contribute to the formation process of the municipality of Palma Sola, SC? The general objective of the research is to understand the participation of the citizen Catharina Crestani Seger in the formation process of the municipality of Palma Sola, SC. Based on it, we outlined the following specific objectives: a) to verify its performance in the area of education and local commerce; b) observe her performance in the area of municipal politics; and c) to investigate Catharina's performance as a woman in the period from 1951 to 1979. The research methodology is of a qualitative nature, adopting bibliographical research, documental research and data analysis through documental analysis as procedures. Two chapters make up the research: the first presents the contributions of the citizen in education and commerce and the second characterizes the contributions in local politics both in the legislative and in the executive. So that the issues of women's performance in society appear in the discussions of both chapters. As a result, it can be considered that Catharina's actions in education, her work in local commerce, and also, the implementations carried out during her work in politics as councilor and mayor contributed to the formation process of Palma Sola, SC. In addition, Catharina's work in commerce and politics was significant in relation to the position of women in Palma Sola society, taking into consideration the historical period present in the time frame, in which women hardly had a prominentsocial representation before men. We also consider that Catharina in that historical time contributed to the process of formation of Palma Sola, it is worth remembering that the data show that many of the echoes of the citizen took place from political articulations that allowed Catharina to be present in spaces of power and knowledge and that helped in the participation of the citizen in different ways. Furthermore, this research was constituted, with the aid of the chosen theoretical contribution, in a systematized organization of Catharina's main contributions when considering educational, commercial and political aspects of Palma Sola.